Stress Analysis of Varian of Plastic Material for Fence Ornament Products Using Finite Element Method - Hendra, Hendra; Ula, Shofiatul; Septiana, Reski (FLYWHEEL : Jurnal Teknik Mesin Untirta, 2025)
Plastic is the most widely used material in Indonesia. The most commonly processed types of plastic are PET (Polyethylene terephthalate), HDPE (High-density polyethylene), and PP (Polypropylene). With advancements in materials technology, plastic is increasingly in demand as a material for fence decoration due to its advantages such as lightness, flexibility, weather resistance, and economy. Using composite materials makes it possible to optimize both strength, flexibility, and resistance to various environmental factors that occur, so as to produce more durable fence ornaments. This study aims to obtain the maximum stress and displacement values of fence ornament products using PP (Polypropylene), PET (Polyethylene Terephthalate), and HDPE (High Density Polyethylene) materials and different variations. And also compare the simulation results of the mechanical test of the fence ornament with the mechanical test conducted in the material laboratory. The finite element method is a numerical method for solving engineering problems of mathematics and physics. This method can be applied to problems with complex geometries, loads, and material properties, which cannot be solved analytically. Simulation results on fence ornament products with PP, PET, and HDPE plastic material composition with a thickness of 10 mm produced a stress value of 61.84 MPa, to the largest 70.26 MPa, and a displacement value of 0.038 mm, to 0.074 mm. In the experimental results obtained a stress value of 14.572 MPa, in the best simulation results obtained a stress value of 63.12 MPa, with a displacement value of 0.038 mm. This can occur due to factors that affect the results of simulation and testing.